Respuesta :

Answer:

s = (i sqrt(439))/16 - 19/16 or s = -(i sqrt(439))/16 - 19/16

Step-by-step explanation:

Solve for s:

1 + 3 s + 8 (s^2 + 2 s + 3) = 0

Expand out terms of the left hand side:

8 s^2 + 19 s + 25 = 0

Divide both sides by 8:

s^2 + (19 s)/8 + 25/8 = 0

Subtract 25/8 from both sides:

s^2 + (19 s)/8 = -25/8

Add 361/256 to both sides:

s^2 + (19 s)/8 + 361/256 = -439/256

Write the left hand side as a square:

(s + 19/16)^2 = -439/256

Take the square root of both sides:

s + 19/16 = (i sqrt(439))/16 or s + 19/16 = -(i sqrt(439))/16

Subtract 19/16 from both sides:

s = (i sqrt(439))/16 - 19/16 or s + 19/16 = -(i sqrt(439))/16

Subtract 19/16 from both sides:

Answer:  s = (i sqrt(439))/16 - 19/16 or s = -(i sqrt(439))/16 - 19/16

ACCESS MORE